The Emirati Family as a Protective System: The Sociology of Intellectual Immunity in the Face of Fluidity in Contemporary Religious Discourse (The International Journal of Educational Sciences and Arts, 2026)
This study examines the Emirati family as a protective social system confronting what has come to be known as the "fluidity of contemporary religious discourse" - a condition in which stable intellectual and religious reference points recede under the pressure of digital openness and the accelerating flow of information. This phenomenon generates multiplicity of channels, diversity of platforms, and fragmented responses, leaving individuals susceptible to rapidly shifting and contradictory ideas.The study proceeds from the premise that the family, as the primary social institution, plays a pivotal role in building a value system and shaping sound religious awareness, thereby contributing to the intellectual immunisation of individuals against the unstable ideological influences generated by digital globalisation and the proliferation of religious knowledge sources.The study adopted a descriptive-analytical methodology supported by an explanatory sequential mixed-methods design. This involved two complementary phases: a quantitative phase using a questionnaire administered to a sample of thirty guardians, and a qualitative phase comprising semi-structured interviews with ten to fifteen specialists from relevant governmental and academic bodies.Findings revealed a high degree of "cognitive vigilance" among Emirati families, with 83.3% demonstrating awareness of the risks of digital fluidity and the proliferation of reference sources. At the same time, the study identified a significant "practice gap": actual digital monitoring did not exceed 53.3%, and 71% of guardians reported deficiencies in digital privacy skills. Results further indicated a high level of trust in official national institutions, reaching 80%, reinforcing an integrative model that links the family system to the institutional apparatus of the state.The study produced a proposed strategic framework entitled "The Fortified Fortress" (Al-Hisn Al-Haseen), grounded in five principles: protective empowerment, organic institutional integration, anticipatory action, national reference, and sustainability. Recommendations were directed at stakeholders and included: establishing a national coordinating council for intellectual immunity; launching programmes for digital parenting competence; developing cognitive discernment curricula in educational institutions; and creating interactive advocacy platforms designed to engage youth in the language of the digital age.
Keywords: Emirati Family; Intellectual Fluidity; Contemporary Religious Discourse; Cognitive Immunity; Protective System; Social Socialisation; National Identity; Intellectual Security; Digital Parental Control; Institutional Integration